Selected Sources of Current Population, Vital, and Health Statistics - Jensen, Marilyn Anne (1972)
This annotated list is a guide to government and nongovernment sources of population, vital, and health statistics. It is arranged first geographically, giving sources for local, regional, state, national, and international statistics, and secondly by issuing body. Below the national level sources for only the California area are included, but they are representative of publications of similar health jurisdictions. The list is selective and concentrates on recent or regularly updated publications. A brief list of guides to other sources is included at the end.